2011
DOI: 10.1302/0301-620x.93b6.25521
|View full text |Cite
|
Sign up to set email alerts
|

Complications and outcome of tibial lengthening using the Ilizarov method with or without a supplementary intramedullary nail

Abstract: We compared the complications and outcome of tibial lengthening using the Ilizarov method with and without the use of a supplementary intramedullary nail. In a retrospective case-matched series assembled from 176 patients with tibial lengthening, we matched 52 patients (26 pairs, group A with nail and group B without) according to the following criteria in order of importance: 1) difference in amount of lengthening (± 2 cm); 2) percentage difference in lengthening (± 5%); 3) difference in patient's age (± seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 27 publications
0
33
1
4
Order By: Relevance
“…However, the concomitant use of an intramedullary nail, such as with tibial LON, can act as a strong resistance to the deforming forces, minimizing axial deviations compared with the classic Ilizarov method. Some studies [2,3,15,20,21] compared the classic Ilizarov method with the LON technique and showed that axial deviation occurred in 4% to 13% of tibias with the classic Ilizarov method, whereas it was 0% to 2% with the LON technique. However, Kim et al [8] reported that they observed 20 segments (14%) that showed valgus angulation with a mean of 10°using the LON technique.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the concomitant use of an intramedullary nail, such as with tibial LON, can act as a strong resistance to the deforming forces, minimizing axial deviations compared with the classic Ilizarov method. Some studies [2,3,15,20,21] compared the classic Ilizarov method with the LON technique and showed that axial deviation occurred in 4% to 13% of tibias with the classic Ilizarov method, whereas it was 0% to 2% with the LON technique. However, Kim et al [8] reported that they observed 20 segments (14%) that showed valgus angulation with a mean of 10°using the LON technique.…”
Section: Discussionmentioning
confidence: 99%
“…It can act as a guide such that the bone is lengthened along the longitudinal axis of the nail with no axial deviations. It was reported that the secondary deformity induced during distraction could be substantively negated with the intramedullary nail in the LON technique of the tibia [3,15,20,21]. However, Kim et al [8] reported that a valgus deviation was the most common complication in 20 segments (25%) in their series of the LON technique of the tibia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…От этого зависит качество и продолжительность лечения, сроки которого не всегда удовлетворяют врачей и самих пациентов. Общий срок лечения па-циентов в зависимости от величины удлинения варьирует от 4 до 18 месяцев [4,5]. Количество возникших трудностей в периоде лечения и ре-абилитации напрямую отражает качество жизни пациентов [6].…”
Section: Introductionunclassified